AN EXPLORATORY STUDY OF COLLECTION DEVELOPMENT OF SELECTED SCHOOL RESOURCE CENTRES IN SRI LANKA - W., Sunil; A.N., Zainab (Malaysian Journal of Library and Information Science, 2002)
Describes the responses from 48 resource managers as well as 183 students from selected schools in the Colombo District, Sri Lanka. As case studies, the researchers also gather information about the collection composition from five selected schools to ascertain the currency and strength of collections in Sri Lankan school resource centres. The results indicate that the majority of school resource centres did not follow any collection development guidelines. The school resource collection is still book-centred and very few possess electronic resources. More than ninety percent of resources are obtained and selected by personnel at the Ministry of Education. The school personnel in the survey did not accept this practice as they prefer to see more empowering of material selection by Special Book Selection Committee or cooperative selection by school teachers and resource managers. The results indicate that both students and teachers do not perceive the current resource collections as adequate for learning and teaching. The collections at the five resource centres indicate that the age of the books are generally less than 10 years and more than fifty percent are published between 1990-2000. This current collection however, does not ensure what has been acquired are relevant to students’ and teachers’ needs. The study proposes that a proper collection policy be drawn up to ascertain that the collection in Sri Lankan resource centers reach at least the minimum universally accepted standard.